Residents' participation in housing in the United Kingdom: Lessons for Nigeria. Issue 3 (2nd April 2020) - Fakere, Alexander Adeyemi
ABSTRACT: Housing is a very important human need along with food and clothing. The process of providing housing should be such that does not alienate the beneficiaries from the process. This study examined residents' participation schemes in the United Kingdom for drawing lessons for the Nigerian housing environment. It used case study method to explore three residents' participation schemes in the UK and collect data for this study. While drawing useful information from approaches and processes of residents' participation in housing in the UK, the paper proposes approaches that can suit the local conditions in Nigeria. Specifically, the paper outlines how policy makers, housing agencies and professionals could adapt the lessons to Nigeria in order to ensure positive outcome from the housing process. It concludes that residents' participation in housing should be more widely practiced in Nigeria to improve the likelihood of meeting the housing needs of residents.